Review papers for journal of risk and financial management (JRFM) - Michael McAleer (Journal of Risk and Financial Management, 2020)
This paper evaluates an editorial and seven invaluable and interesting review papers for the Journal of Risk and Financial Management (JRFM). The topics covered include the rising complexity of bank regulatory capital requirements from global guidelines to their United States (US) implementation, connections among big data, computational science, economics, finance, marketing, management and psychology, factors, outcome, and the solutions of supply chain finance, with a review and future directions, time-varying price-volume relationship, adaptive market efficiency, and a survey of the empirical literature, improved covariance matrix estimation for portfolio risk measurement, stock investment and excess returns, with a critical review in the light of the efficient market hypothesis, and a cross section analysis of country equity returns, and a review of the empirical literature.
Keywords: 330; adaptive market efficiency; bank regulatory capital requirements; big data; computational science; country equity returns; covariance matrix estimation; economics; efficient market hypothesis; excess returns; finance; management; marketing; portfolio risk measurement; price-volume relationship; psychology; stock investment; supply chain finance